Effects of different organic acids on the survival growth, and histopathology of red hybrid tilapia (Oreochromis sp.) - Nor Hafizah Daeman (2016)
A 63 day experiment was conducted to determine the effects of different dietary organic acids on the survival, growth, muscle proximate composition, muscle cholesterol, muscle TBARS, plasma biochemistry, intestinal short chain fatty acids (SCFA) and liver histopathology of tilapia. A total of 5 diets, which consisted of propionic acid, formic acid, butyric acid, or acetic acidwere formulated with 2% supplementations and a control diet with no organic acid additions. Each treatment was triplicated with total of 20 tilapia of (2 – 5 cm) in each. Results showed that the survival was high (95.0 – 98.3%) and the fish more than tripled in size, but no differences among treatments were found (p > 0.05). Plasma glucose was significantly higher (p < 0.05) for tilapia fed the dietary formate compared to the control or others. Among the proximate composition, crude muscle protein and lipid were significantly lower and higher, respectively, for fish fed the formic acid diet. In addition, the liver of fish fed the formate diet showed inflammatory responses and lipofuscin-like material as well as significantly higher glycogen content. The intestinal SCFAs, which included acetic, propionic and butyric acid, all significantly decreased (p < 0.05) in all the dietary organic acid treatments. Finally, with the exception of the acetate treatment, the muscle from fish fed all the organic acid diets had significantly less lipid peroxidation compared to the control. Among all the organic acids, dietary formate appeared to have some toxic effects while dietary propionate may be advantageous since this led to significantly lower muscle cholesterol, without compromising growth, as well as significantly less lipid peroxidation which should improve the shelf-life of tilapia products.